Оцінка якості користувацького інтерфейсу - Діденко, М. В. (My University, 2020)
One of the best approaches to the quantitative analysis of interface models is the classic GOMS model. The method allows you to predict how long it will take the user to perform a specific operation when using this interface model
Keywords: оцінка якості; користувацький інтерфейс